PENDAMPINGAN PASTORAL ORANG MENJELANG AJAL - Romas, Romanus (STIPAS TAHASAK DANUM PAMBELUM KEUSKUPAN PALANGKARAYA, 2017)
Death remains a mystery to human. The shattering in the face of death isoften a terrific struggle, especially for the dying, as well as for relatives, andthe medical personnel involved. Attempts to accompany, deliver or face thedeath peacefully are not easy. Many problems are faced around this issue. Sothatâs why Pastoral care is important for those who are on the threshold of life.